1990
DOI: 10.1111/j.1478-4408.1990.tb01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow of foam through plain perforated and woven metal screens

Abstract: The interaction of foam with textile substrates has been investigated, starting with an attempt to describe the flow of foam in textile–like substrates. This was done by separately evaluating rheology and pressure–drop data. The influence of bubble size was found to be particularly important. In a coaxial cylinder viscometer the viscosity was found to be inversely proportional to bubble size. This finding could not be used to describe the pressure drop of foam flow through flat metal screens according to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Foam is used for this purpose for example in the non-woven industry for carrying long fibers (Hanson 1977), for displacing and transporting oil in enhanced oil recovery (Farajzadeh et al 2012), and transporting chemicals in remediation of soils (Geraud et al 2015). Moreover, air bubbles are widely used for separation of mixtures through flotation (Lemlich 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Foam is used for this purpose for example in the non-woven industry for carrying long fibers (Hanson 1977), for displacing and transporting oil in enhanced oil recovery (Farajzadeh et al 2012), and transporting chemicals in remediation of soils (Geraud et al 2015). Moreover, air bubbles are widely used for separation of mixtures through flotation (Lemlich 1972).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if the bubbles are bigger than the pores, the flow consists of the movement of individual bubbles and bubble deformations. Lemmen and Wassink [88] studied the flow of foam through metal screens. They found that the theoretical values of pressure loss calculated using the measured rheological behavior of foam was too high by a factor of two when compared with experiments.…”
Section: Flow Of Foam In Real Geometriesmentioning
confidence: 99%
“…[86] (b) Foam flow in a fibrous porous material is a combination effect of bulk foam viscosity and bubble distortion. [88] Reprinted from Ref. [86] under the terms of the CC BY 4.0 license (http://creativecommons.org/licenses/by/4.0/).…”
Section: Mixing Effects On Generated Foam Structurementioning
confidence: 99%